Qualidade de vida em portadores de doença falciforme - Menezes, Adeline Soraya de Oliveira da Paz [UNIFESP] (2011)
Objective. 1) To evaluate the quality of life in children and adolescents with sickle cell disease attending the Blood Center reference. 2) To evaluate the quality of life of relatives of these patients. Method. We selected 100 patients (64 female, 34 male) with sickle cell disease that were divided into three subgroups with age: 5 to 7 (n = 18), 8-12 (n = 32) and 13 to 18 (n = 20), and their parents. The control group was 50 healthy children and adolescents from a public school local, also divided into the same three subgroups of age and their caregivers. The Questionnaire Pediatric Quality of life Inventory - PedsQL version 4.0 was applied in both groups - children and adolescents, in the family was applied the generic questionnaire Medical Outcomes Study 36 - Item Short-Form Health Survey (SF-36). The answers were linearly transformed into a score and compared. Results: The scores of patients were significantly lower than the scores of the control group (p <0.0001) in all four areas studied (physical, emotional, social and school activities). In the version for parents was the same in almost all respects, with the loss of quality of life more meaningful (more than 50%) were related to the socio-emotional, mental health, limited by the physical appearance and general state of health. Conclusion: Sickle cell disease affects the quality of life of children, adolescents and their families. Patients perceive restrictions in the emotional, social / family and physical and others.